PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENUMBUHKAN KEDISIPLINAN GURU DAN KARYAWAN - andriyani, andriyani; Sulistyaningrum Indrawati, Cicilia Dyah; Susilowati, Tutik (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The objective of this research is to investigate: (1) the leadership role of the headmaster in growing the discipline of the teachers and the administrative staff members of SMK Negeri 1 of Surakarta; (2) the obstacles in the leadership role of the headmaster in growing the discipline of the teachers and the administrative staff members of SMK Negeri 1 of Surakarta; (3) the solution from the role of the headmaster to overcome the obstacles which emerge in actualizing the discipline of the teachers and the administrative staff members of SMK Negeri 1 of Surakarta. This research used the descriptive qualitative method and the embedded single research strategy. The population of this research was the headmaster, the teachers, the administrative staff members, and the students of SMK Negeri 1 of Surakarta. The samples of this research were taken by using the purposive sampling technique. The data of this research were gathered through interview, observation, document analysis from informants, places, events, documents, and files. The data were then analyzed by using the interactive analysis technique. The results of this research are as follows: (1) the leadership role of the headmaster of SMK Negeri 1 of Surakarta was done through the activities of discipline building, such as: (a) giving motivation to the teachers and the administrative staff members; (b) giving the leadership role model by having discipline; (c) making efforts in paying attention to the welfare of the teachers and the administrative staff members; and (d) implementing discipline enforcement; (2) the obstacles which emerge in building discipline in SMK Negeri 1 of Surakarta are as follows: (a) the internal obstacles, such as: the characters of personality of some teachers and administrative staff members which are difficult to accept advice and less responsible in doing their job and tasks; and (b) the external obstacles which emerge in building the discipline of the teachers and the administrative staff members of SMK Negeri 1 of Surakarta; and (3) the solutions to overcome the obstacles are as follows: (a) enforcing the rule and making discipline development; and (b) intesifying the shared activities with the teachers and the administrative staff members.Keywords: principal's leadership role, Teacher and Employee Discipline